PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN SUZUKI CARRY SAAT PANDEMI COVID-19 DI PROVINSI JAWA BARAT - Christian Daniel Halomoan Hutagalung (2021)
This study describes a quantitative research that aims to be able to identify the effect of product quality and price on purchasing decisions for Suzuki carry when the Covid-19 pandemic is taking place in West Java province. With a population of 50 Suzuki consumers who purchase Suzuki carry in West Java province respondents. The sample collection uses saturated samples, which means that all populations are sampled. Data were collected by distributing questionnaires, and distributed to several dealers in West Java. Data testing was performed using PLS (Partal Leat Suare) analysi, with the SmartPLS3.0 program with a significance level of 5% (0.05). The results of this data processing indicate that (1) product quality has a signifcant efect on purchasing decisions, and (2) price has a significant effect on purchasing decisions. This study also shows the R square value of 0.677. Where the variables of product quality and price have an influence of 67% on purchasing decisions, and 33% are influenced by other variables such as promotion, brand image, and advertising.. Keywords : Product Quality, Price, Purchasing Decision, Vehicle, Covid-19